2019
DOI: 10.1021/acs.orglett.9b01645
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene Ligand-Controlled Regioselectivity for Nickel-Catalyzed Hydroarylation of Vinylarenes with Benzothiazoles

Abstract: A facile regioselective switch for nickel-catalyzed hydroarylation of vinylarenes with benzothiazoles has been developed, which relies on the simple structural variation of novel Ni­(II) complexes of the type Ni­(NHC)­[P­(OR)3]­Br2. Using magnesium turnings as the reductant, Ni­(IMes)­[P­(OEt)3]­Br2 afforded branched products, while Ni­(IPr*OMe)­[P­(OEt)3]­Br2 created steric demand to afford linear products. This work also provides a rare example of the rational design of heteroleptic Ni­(II) complexes that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…A catalytic mixture consisting of Ni­(COD) 2 , IPr (NHC) and P­(OPh) 3 , applied to reductive alkene/aldehyde coupling reactions, has recently been described in which a nickel NHC-phosphite (1:1) intermediate is proposed as part of the catalytic cycle . Additionally, nickel-catalyzed hydroarylation of benzothiazoles has very recently been explored with halogenated Ni­(II) precursors containing P­(OEt) 3 and NHC ligands . If nickel(0) NHC-phosphite complexes could be isolated, their further catalytic ability could be fully explored in a range of reactions.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A catalytic mixture consisting of Ni­(COD) 2 , IPr (NHC) and P­(OPh) 3 , applied to reductive alkene/aldehyde coupling reactions, has recently been described in which a nickel NHC-phosphite (1:1) intermediate is proposed as part of the catalytic cycle . Additionally, nickel-catalyzed hydroarylation of benzothiazoles has very recently been explored with halogenated Ni­(II) precursors containing P­(OEt) 3 and NHC ligands . If nickel(0) NHC-phosphite complexes could be isolated, their further catalytic ability could be fully explored in a range of reactions.…”
Section: Introductionmentioning
confidence: 88%
“…31 Additionally, nickel-catalyzed hydroarylation of benzothiazoles has very recently been explored with halogenated Ni(II) precursors containing P(OEt) 3 and NHC ligands. 32 If nickel(0) NHC-phosphite complexes could be isolated, their further catalytic ability could be fully explored in a range of reactions. Herein, we report the synthesis and characterization of the first isolable, low-valent, mixed nickel NHC-phosphite systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The authors were able to isolate and characterize the active catalyst by single-crystal X-ray crystallography (Scheme 59). Similarly, Sun and coworkers also employed a NHCs-based nickel catalytic system for the regioselective hydroarylation of vinylarenes with benzothiazoles, affording the desired product in high yield [92]. In this reaction, the regioselectivity is controlled by the sterically demanding Ni(IMes)[P(OEt)3]Br2 catalyst (Scheme 60).…”
Section: Scheme 60 Ni-catalyzed Hydroarylation Of Vinylarenes With Benzothiazolesmentioning
confidence: 99%
“…Mechanistic studies indicated that the main step is the formation of a Cu(I) carbene species, followed by migratory insertion and protonation to produce the final products, as shown in Scheme 61. Similarly, Sun and coworkers also employed a NHCs-based nickel catalytic system for the regioselective hydroarylation of vinylarenes with benzothiazoles, affording the desired product in high yield [92]. In this reaction, the regioselectivity is controlled by the sterically demanding Ni In 2017, Mandal and coworkers developed a Ni(COD)2 catalyzed regioselective hydroheteroarylation of vinylarenes with benzoxazoles, providing an exclusively wide range of 1,1diarylethane products [91].…”
Section: Scheme 60 Ni-catalyzed Hydroarylation Of Vinylarenes With Benzothiazolesmentioning
confidence: 99%
“…Since the first example of the ortho -C–H alkylation of aromatic ketones with alkenes using Ru catalysis, a large number of reports on directed C–H alkylation with alkenes have appeared. However, most of these reactions were based on a linear-selective transformation, and only a limited number of studies have dealt with a branch-selective transformation. , In addition, the reported branch-selective alkylation reactions mostly involved the use of activated alkenes such as styrenes, acrylate esters, and vinyl esters. Our group recently reported the first example of the branch-selective alkylation of sulfonamides with vinylsilanes (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%